Emotion regulation in response to daily negative and positive events in youth: The role of event intensity and psychopathology. (September 2021) - Hiekkaranta, Anu P.; Kirtley, Olivia J.; Lafit, Ginette; Decoster, Jeroen; Derom, Catherine; de Hert, Marc; Gülöksüz, Sinan; Jacobs, Nele; Menne-Lothmann, Claudia; Rutten, Bart P.F.; Thiery, Evert; van Os, Jim; et al.
Abstract: Environmental and individual contextual factors profoundly influence how people regulate their emotions. The current article addresses the role of event intensity and psychopathology (an admixture of depression, anxiety, and psychoticism) on emotion regulation in response to naturally occurring events. For six days each evening, a youth sample (aged 15–25, N = 713) recorded the intensity of the most positive and most negative event of the day and their subsequent emotion regulation. The intensity of negative events was positively associated with summed total emotion regulation effort, strategy diversity, engaging in rumination, situation modification, emotion expression, and sharing and negatively associated with reappraisal and acceptance. The intensity of positive events was positively associated with strategy diversity, savoring, emotion expression, and sharing. Higher psychopathology symptoms were only related to ruminating more about negative events. We interpret these findings as support for the role of context in the degree of effort and type of emotion regulation that young people engage in. Highlights: A daily diary study of a large sample of adolescents and emerging adults. Event intensity is a key factor in emotion regulation effort and strategy choice. Intensity of positive events is associated with more emotion upregulation. Controlling for intensity, psychopathology is associated with more rumination.